Pharmacological characterization of LPS and opioid interactions at the toll‐like receptor 4. (25th February 2013) - Stevens, CW; Aravind, S; Das, S; Davis, RL
<x xml:space="preserve">Abstract</x> Background and Purpose Previous work in our laboratory showed opioid agents inhibit cytokine expression in astrocytes. Recently, Watkins and colleagues hypothesized that opioid agonists activate toll‐like receptor 4 (TLR4) signalling, which leads to neuroinflammation. To test this hypothesis, we characterized LPS and opioid effects on TLR4 signalling in reporter cells. Experimental Approach NF‐κB reporter cells expressing high levels of TLR4 were used to compare LPS and opioid effects on NF‐κB activation, a pathway activated by TLR4 stimulation. Key Results LPS increased TLR4 signalling in a concentration‐dependent manner and was antagonized by LPS antagonist (LPS‐RS, from Rhodobacter sphaeroides). A concentration ratio analysis showed that LPS‐RS was a competitive antagonist. The opioid agonists, morphine and fentanyl, produced minor activation of TLR4 signalling when given alone. When tested following LPS stimulation, opioid agonists inhibited NF‐κB activation but this inhibition was not blocked by the general opioid antagonist, naloxone, nor by the selective μ opioid receptor antagonist, β‐FNA. Indeed, both naloxone and β‐FNA also inhibited NF‐κB activation in reporter cells. Further examination of fentanyl and β‐FNA effects revealed that both opioid agents inhibited LPS signalling in a non‐competitive fashion. Conclusions and Implications These results show that LPS‐RS is a competitive antagonist at the TLR4 complex, and that both opioid agonists and antagonists inhibit LPS signalling in a non‐competitive fashion through a non‐GPCR, opioid site(s) in the TLR4 signalling pathway. If confirmed, existing opioid agents or other drug molecules more selective at this novel site may provide a new therapeutic approach to the treatment of neuroinflammation.